Pendekatan Psikologis dalam Pembelajaran PAI untuk Membangun Karakter dan Kebermaknaan Belajar - Ikke Seli Livia; Nur-Inee Tukaebusi; Ma`mun hanif (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2026)
This article discusses Islamic Religious Education (PAI) materials using a psychological approach to improve students' understanding of religious teachings. This study examines five important aspects: (a) psychologists' perspectives on religion, highlighting its role in shaping identity and mental well-being; (b) adapting PAI materials to students' developmental stages, which is crucial for ensuring that religious teachings are easily accepted and understood; (c) evaluating PAI materials based on interests and talents, which aims to increase student motivation and engagement; (d) a PAI model that focuses on comfort in religious practice, which aims to build a positive relationship between students and religious teachings; and (e) the role of PAI teachers as spiritual advisors who support students' mental and spiritual health. With this approach, religious education can serve as a spiritual foundation and provide ongoing psychological support. This article is expected to serve as a reference for teachers and education practitioners in developing more effective and relevant PAI materials.